Selected plant triterpenoids and their amide derivatives in cancer treatment: A review - Özdemir, Zulal; Wimmer, Zdeněk (Phytochemistry, 2022)
Medicinal plants have been used to treat different diseases throughout the human history namely in traditional medicine. Most of the plants mentioned in this review article belong among them, including those that are widely spread in the nature, counted frequently to be food and nutrition plants and producing pharmacologically important secondary metabolites. Triterpenoids represent an important group of plant secondary metabolites displaying emerging pharmacological importance. This review article sheds light on four selected triterpenoids, oleanolic, ursolic, betulinic and platanic acid, and on their amide derivatives as important natural or semisynthetic agents in cancer treatment, and, in part, in pathogenic microbe treatment. A literature search was made in the Web of Science for the given key words covering the required area of secondary plant metabolites and their amide derivatives. The most recently published findings on the biological activity of the selected triterpenoids, and on the structures and biological activity of their relevant amide derivatives have been summarized therein. Mainly anti-cancer effects, and, in part, antimicrobial and other effects of the four selected triterpenoids and their amide derivatives have also been reviewed. A comparison of the effects of the parent plant products and those of their amide derivatives has been made.
Keywords: nádory; Oleanolic Acid; Humans; léčivé rostliny; Cytotoxicity; Triterpenes; Medicinal plant; Antimicrobial activity; Amide; triterpeny; Plants, Medicinal; amidy; lidé; Neoplasms; Hepatitis a virus; Pentacyclic triterpenoid; kyselina olenalová; Amides; Secondary metabolite; Antimalarial activity